Ethical Implications of Obstetric Care in Hungary: Results from the Mother-Centred Pregnancy Care Survey - Szebik, Imre; Susánszky, Éva; Szántó, Zsuzsa; Susánszky, Anna; Rubashkin, Nicholas (European Journal of Mental Health, 2018)
Background: Informed consent plays an important role in clinical decision making. It is a basis of self determination in health care. In ideal situations health care professionals inform their patients about all relevant aspects of care and alternative care options, map the value system of the patients, and adjust the information process accordingly. Objectives: Our objective was to see the frequency of selected interventions (birth induction, caesarean section, episiotomy, forced supinal position during birth, and the consent process associated to these interventions. Methods: 1,257 women (with childbearing capacity) between the age of 18 and 45 with children under the age of 5 were surveyed online. Results: Caesarian section was done without permission in 10.2% of women. Labour was inducted in 22.2% of all deliveries and it was done without permission in 25.4% . Episiotomy was done in 39.9% of women having vaginal delivery in the Sample 2 group and in 72.2% of women having vaginal delivery in the Sample 1 (representative) group. Women undergoing episiotomy were not asked for consent in 62.0% in the Sample 1 group and in 57.1% in the Sample 2 group. Freedom to choose labour position for women having vaginal birth was restricted in 65.7% in the Sample 1 group and in 46% in the Sample 2 group. Discussion and Conclusions: We have found that the right of women to informed consent and best available treatment is frequently and seriously violated in obstetric practice in Hungary in the given period. These findings should serve as an important basis for improving the quality of maternity care.